EXPLORING YOUTH INTENTION TOWARD SELF-EMPLOYMENT IN INDONESIA: EVIDENCE FROM SUSENAS MICRODATA - Muara Setyanti, Axellina; Finuliyah, Firdaus; Afif Khoiruddin, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2024)
This study examines the determinants of youth intentions toward self-employment using data from the 2022 Survei Sosial Ekonomi Nasional (SUSENAS). The analysis draws from a robust sample of more than 200.000 individuals aged 16 to 30, as defined by Indonesia’s Law No. 40/2009 on Youth. Logistic regression analysis was employed to investigate the influence of various socio-economic factors on self-employment intentions. The results reveal that demographic characteristics such as gender, marital status, and household size significantly affect entrepreneurial aspirations, with rural youth showing stronger effects than their urban counterparts. Financial factors, particularly saving behavior and access to credit, also play a pivotal role in promoting self-employment intentions. Interestingly, while education and internet access exhibit mixed effects, geographic differences highlight the varying challenges faced by rural and urban youth. These findings underscore the complex interplay between socio-economic factors and entrepreneurial intentions, offering key insights for policymakers aiming to foster youth entrepreneurship across Indonesia's diverse regions.